What is the best hypnotic in elderly patients?. Issue 1 (January 2016) - Hanson, Christopher J.; Malone, Sara
Abstract : Evidence‐Based Answer : Benzodiazepines and "z‐class" sedatives (zolpidem, zopiclone, and zaleplon) are the most efficacious sleeping medications in terms of sleep latency and increase total sleep time by approximately 30 minutes, but may cause more harm than benefit (SOR: A, metaanalysis of RCTs). However, there does not appear to be an increased mortality risk with their use (SOR: B, single cohort study). Ramelteon appears to be less beneficial, but with fewer reported side effects (SOR: A, systematic review of RCTs).